Fundamental of Entrepreneurship ENT300 : Rainbow Kids Kindergarten / Nur Aznalia Azura Azhar ... [et al.] - Azhar, Nur Aznalia; Haris, Nurfaradila; Saleh, Noor Salinah; Jikus, Norslyvien Eva; Abd.Hamid, Nadiah (2007)
After doing an extensive research of the business opportunity that available in Kuching, our group has made decision to specify our business in selling our services. Our group has decide to come up with the business plan of partnership where by our organization will be known as ‘Rainbow Kids Kindergarten’. In order to make our business real success, we have seriously taken into consideration all of the aspects specially the four major of business establishment, such as administration, marketing, operation and finance. All of these aspects are very important as it is can be considered as the backbone of the business. That is also why we come out with the business plan, so that we can manage the business properly.